Phineas Fletcher. Locustae vel Pietas Iesuitica - Haan, E.(ed.) (Supplementa Humanistica Lovaniensia, 1996)
The bilingual English poet Phineas Fletcher (1582-1650) is the author of a short Latin epic on the Gunpowder Plot (1605). Mrs. Estelle Haan has provided the first critical edition based on all three manuscripts known and the original printed edition (Cambridge, 1627). After the introduction with an essay on the Gunpowder Plot literature in Latin (including poets, such as John Milton) follows the critical edition of Locustae vel Pietas Iesuitica with an English translation and an extensive commentary.